2023
DOI: 10.3390/en16093616
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Assessment of Hellisheidi Geothermal Power Plant based on Exergy Allocation Factors for Heat and Electricity Production

Abstract: The Hellisheidi geothermal power plant, located in Iceland, is a combined heat and power double-flash geothermal plant with an installed capacity of 303.3 MW of electricity and 133 MW of hot water. This study aimed to elucidate the environmental impacts of the electricity and heat production from this double-flash geothermal power plant. In this vein, firstly, the most updated inventory of the plant was generated, and secondly, a life-cycle assessment approach based on the exergy allocation factor was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Despite the Nesjavellir GPP being a combined heat and power (CHP) plant, this study does not describe the three more common allocation methods used in LCA evaluations (i.e., energy, exergy and economic allocations) for this type of energy plant [33]. Instead, this paper focuses exclusively on exergy allocation to assess the environmental burden of electricity and heat from the geothermal CHP plant, as it is the one that is more recently in use and not extensively reported in the literature [16,17,34].…”
Section: Environmental Evaluation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the Nesjavellir GPP being a combined heat and power (CHP) plant, this study does not describe the three more common allocation methods used in LCA evaluations (i.e., energy, exergy and economic allocations) for this type of energy plant [33]. Instead, this paper focuses exclusively on exergy allocation to assess the environmental burden of electricity and heat from the geothermal CHP plant, as it is the one that is more recently in use and not extensively reported in the literature [16,17,34].…”
Section: Environmental Evaluation Methodologymentioning
confidence: 99%
“…This study analyses the Nesjavellir geothermal power plant (GPP) as it replicates the solution that is already implemented in the Hellishedi geothermal power plant [16,17]. The innovations applied to this power plant are Carbfix [18] and Sulfix [19], which aim to minimise the emissions of CO 2 and H 2 S, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Díaz-Ramírez et al [96] conducted an environmental evaluation of the Hellisheidi geothermal power plant using exergy allocation factors. The geothermal plant, a combined heat and power double-flash facility located around 30 km east of Reykjavik, Iceland's capital, has an installed capacity of 303.3 MW of electricity and 133 MW of heat.…”
Section: Energy Saving In Buildingsmentioning
confidence: 99%
“…Despite a small decrease in electricity production, the AHP scenario offers improved efficiency and a potential increase in total electricity generated by over 0.4%. The study performed by Diaz-Ramirez et al [78] used a life-cycle assessment approach based on the exergy allocation factor, considering all life-cycle stages from construction to dismantling. The results showed that most of the environmental impact was attributed to electricity production, and the construction stage was the most impactful.…”
mentioning
confidence: 99%